Detection for haemagglutinating viruses from bats in selected areas in Kuching and Samarahan division - Priscilla Lensi, Rogers (Universiti Malaysia Sarawak, (UNIMAS), 2008)
A total of 37 oral and rectal swabs, and tracheal, lung and intestinal tissues were obtained from bats, Cynopterus brachyotis (n=24), Balionycteris maculata (n=9),Hipposideros cervinus (n=1), EOnycteris spelaea (n-l) and Hipposideros sabanus (n=2), for detection of haemagglutinating viruses via in QYQ Propagation. The results for haemagglutinating spot test showed absence of haemagglutinating viruses. The results for enzyme-linked immunosorbent assay also showed absence of antibody against haemagglutinating viruses that might have cross-reactions with Newcastle disease virus.